Big red apple - Johnston, Tony, 1942-; Corwin, Judith Hoffman (New York : Scholastic, 2003)
The wind blows an apple off a tree, a worm eats a tiny hole in it, a bird pecks at it, and a boy eats it, spitting out the seeds--from which an apple tree grows.
G1
Keywords: Apples -- Fiction